Acute pulmonary embolism following acute type A aortic dissection in a patient with COVID‐19. Issue 4 (2nd February 2021) - Volvovitch, David; Ram, Eilon; Cohen, Hillit; Kogan, Alexander; Sternik, Leonid; Raanani, Ehud
Abstract: Acute aortic dissection and acute pulmonary embolism (PE) are life‐threatening emergencies that can mimic each other at presentation. Immediate and accurate diagnosis of these scenarios is crucial to initiate the appropriate interventions. In this case report we present a 73‐year‐old patient, who was admitted to our Medical Center with acute type A aortic dissection. She was tested for coronavirus disease 2019 (COVID‐19) infection and was found to be positive. During her admission in the COVID‐19 designated intensive care unit, she diagnosed with acute PE in the main right and left pulmonary arteries. She underwent surgery that included bilateral pulmonary embolectomy and aortic dissection repair. The patient was discharged from our hospital on the ninth postoperative day without any complications. Frequency of simultaneous presentation of acute aortic dissection and acute PE is increased with a history of coagulation abnormalities as seen in patients with COVID‐19.